A meeting at risk: Unrepaired DSBs go for broke. (2nd November 2017) - Guénolé, Aude; Legube, Gaëlle
ABSTRACT: Translocations are dramatic genomic rearrangements due to aberrant rejoining of distant DNA ends that can trigger cancer onset and progression. Translocations frequently occur in genes, yet the mechanisms underlying their formation remain poorly understood. One potential mechanism involves DNA Double Strand Break mobility and juxtaposition (i.e. clustering), an event that has been intensively debated over the past decade. Using Capture Hi-C, we recently found that DSBs do in fact cluster in human nuclei but only when induced in transcriptionally active genes. Notably, we found that clustering of damaged genes is regulated by cell cycle progression and coincides with damage persistency. Here, we discuss the mechanisms that could sustain clustering and speculate on the functional consequences of this seemingly double edge sword mechanism that may well stand at the heart of translocation biogenesis.